منهج أبي داود في تخريج مرويات "التراجم المعلة" في كتابه "السنن" سماك بن حرب عن عكرمة نموذجا: ABŪ DĀWŪD’S METHODOLOGY IN RECORDING NARRATIONS FROM AL-TARĀJIM AL-MU‘ALLAH IN “AL-SUNAN”: A SAMPLE STUDY ON NARRATIONS OF SIMĀK IBN ḤARB FROM ‘IKRIMAH - Hanaffie Bin Hasin; Basim Faisal al-Jawabrah (Maʿālim al-Qurʾān wa al-Sunnah, 2022)
One of the significant criteria of an authentic ḥadīth is, it is free from any syudzūdz and ‘illah in its sanad or matn, and this criterion is related to one important criterion, which is ḍabṭ al-rāwi. A ḥadīth narrator is categorized into different levels and groups based on his ‘adālah and ḍabṭ, and hence his narrations will be labeled as Ṣaḥīḥ, Ḥasan, or Ḍa‘īf. There is a group of generally trustworthy ḥadīth narrators, but their narrations in certain circumstances are considered inadequate due to poor memory. Simāk Ibn Ḥarb falls under this category. According to most ḥadīth scholars, he is a trustworthy narrator, and his narrations are in significant ḥadīth encyclopedias. Unfortunately, his narrations from his teacher, ‘Ikrimah mawla Ibn ‘Abbās, are inconsistent; therefore, some of the ḥadīth experts like al-Bukhāri and Muslim, the authors of the two most authentic ḥadīth books, did not record any narration from this chain in their books, and they classified this chain as a defected one. At the same time, other ḥadīth scholars like the authors of al-Sunan al-Arba’ah, Ibn Khuzaymah, and Ibn Ḥibbān, the authors of two ṣaḥīḥ books, recorded a considerable number of his narrations from this chain. This scenario raises an inevitable question regarding the reason and methodology of these scholars in doing so despite their knowledge of the problematic chain. In this study, I will examine thirteen narrations of this chain in the book of al-Sunan by Abū Dāwūd, which is one of the essential ḥadīth books in Islamic tradition. After thoroughly studying the narrations, I conclude that Abū Dāwūd had recorded those narrations where he was confident that Simāk Ibn Ḥarb had memorized them properly from his teacher, Ikrimah, based on the syawāhid and mutāba’ah. As for the sole narrations from this chain, Abū Dāwūd recorded them because the practices of some fuqahā’ support them or because the ḥadīth is under the mursal category, which is considered sufficient as fiqh evidence. This methodology is known as al-intiqā’, where a ḥadīth scholar will choose some narrations from a narrator or a chain, after being confident that the content of the narrations is accurate. Thus, it is unmethodological to impose a general ruling on each narration from this chain as weak without thoroughly examining them case by case, especially if the narration is in a ṣaḥīḥ book or al-sunan al-arba’ah.